1999
DOI: 10.1177/104649649903000205
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Questions Asked During Small Decision-Making Group Discussions

Abstract: Sixty minutes each of group discussions from 18 four- to seven-member decision-making groups were audiotaped and transcribed for analysis. Results indicated that questions constituted 15.6% of total turns by group members. Probes were the most frequently occurring question type (89.2%). There was a significant gender difference in only one of the five question types: Female group members asked significantly more probing questions than did their male counterparts. Implications of these findings are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 35 publications
1
23
0
2
Order By: Relevance
“…These results are similar to the results obtained in other studies regarding the social atmosphere in work groups (Gillies & Ashman, 1996;Järvenoja & Järvelä, 2005;Kreijns et al, 2004;López & Álva-rez, 2009;Van Gennip et al, 2010), the perception of efficacy regarding the management of available time (Wang & Lin, 2007;Yoon & Johnson, 2008), the positive impact of an adequate distribution of roles and an interaction format that favors positive interdependence among group members on cooperative work (Aritze ta & Balluerka, 2006; Arvaja et al, 2007), and the effect of females in a group on improving the levels of cooperation (Hawkins, 1999;Mebane et al, 2007;Olaniran, 1995;Savicki & Kelley, 2000).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…These results are similar to the results obtained in other studies regarding the social atmosphere in work groups (Gillies & Ashman, 1996;Järvenoja & Järvelä, 2005;Kreijns et al, 2004;López & Álva-rez, 2009;Van Gennip et al, 2010), the perception of efficacy regarding the management of available time (Wang & Lin, 2007;Yoon & Johnson, 2008), the positive impact of an adequate distribution of roles and an interaction format that favors positive interdependence among group members on cooperative work (Aritze ta & Balluerka, 2006; Arvaja et al, 2007), and the effect of females in a group on improving the levels of cooperation (Hawkins, 1999;Mebane et al, 2007;Olaniran, 1995;Savicki & Kelley, 2000).…”
Section: Discussionsupporting
confidence: 81%
“…Los estudios muestran que existen diferencias significativas entre géneros con respecto a los resultados asocia-dos a una tarea cooperativa. Por ejemplo, la investigación indica que en contraste a los hombres, las mujeres tienen una percepción más positiva de los resultados globales al finalizar una actividad cooperativa (Olaniran, 1995), aprenden más trabajando cooperativamente (Harskamp, Ding, y Suhre, 2008), realizan más preguntas y valoran más las opiniones de los demás miembros del grupo, planifican mejor las tareas (Hawkins, 1999) . Según estos estudios se pueden distinguir diferentes estructuras de interacción, tales como estructuras independientes (algunos miembros ofrecen información parcial), estructuras de adición complementaria (todos los miembros ofrecen su información), estructuras de intercambio complementario (la información es agregada, ordenada y conectada), estructuras de integración cooperativa (se añade cohesión y coherencia a la información ya conectada) y estructuras de transformación cooperativa (la información se discute y parafrasea para producir una sín-tesis personalizada y completa) (Hadwin y Järvenoja, 2011).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…In addition to the gender of the person coordinating the meeting, it appears that the style of coordination and/or type of leadership of the meeting coordinator has a decisive influence on the quality of participation and decision-making. Broadly speaking, and taking due caution into account, it is possible to distinguish a 'female style' of participation, which matches results obtained by Hawkins and Power (1999). This style is characterised by the use of direct and concise contributions, a search for dialogue and consensus, articulation of more pragmatic approaches, as well as concern for aspects related to the process and not just with the contents of decision-making.…”
Section: Discussionmentioning
confidence: 87%
“…No differences were found between malemale and male-female dyads on any variable. Hawkins and Power (1999) analysed the questions formulated in decision-making meetings and found that although there were no significant differences between the number of questions posed by men and women; however, there were differences as to the type of questions asked. Women tended to ask questions of an exploratory nature, inviting others to produce arguments and share information and opinions, giving an opportunity for others to exercise their influence.…”
Section: Introductionmentioning
confidence: 99%